Productivity and precocity accessions of spring wheat in the environmental testing of spring wheat in contrasting conditions of Kazakhstan. (Eurasian Journal of Ecology, 2016)
A complex selection estimation of 37 accessions under LLP «KazNIIZiR» Aktobe SKHOS and Karabalyk SKHOS productivity, precocity. The studies highlighted in genotypes with good environmental adaptability, who have proven themselves in terms of two contrasting areas in terms of productivity and in certain conditions in which they can be cultivated. Most precocious accessions Trenr, Saratov 55, Saratov 60, Saratov 70, 39 Aktobe, manifested in two ecological zones will be used in the selection of spring wheat as genetic sources of increasing productivity and precocity.
Keywords: Ecology; spring wheat; line; grade; genotype; productivity; selection; growing season